Unexpected failure of cast superduplex stainless steel exposed to high chlorides containing water: From failure analysis to corrosion mechanisms settlement. (June 2022) - Lanzutti, A.; Andreatta, F.; Magnan, M.; Gerolin, A.; Fedrizzi, L.
Highlights: The failure analysis of a cast superduplex stainless steel valve has been performed. The valve failed in proximity of a bar welded on a cast body. Segregated areas with different PREN in ferritic phase has been found. The segregated area is less noble and corrodes preferentially. The cast material showed severe pitting corrosion in immersion tests at 60 °C. Abstract: This work deals with the failure analysis of a super duplex valve operating in technical waters with high chlorides content up to 80 °C. A careful fracture surfaces and microstructural characterization was combined with corrosion studies (SKPFM (Scanning Kelvin Probe Force Measurements) and polarization curves) of different valve regions in order to determine the failure mechanism. It was found that the cast material presents a segregated microstructure containing ferritic phases with different PREN (Pitting Resistance Equivalent Number). This strongly affects the corrosion properties of the material, enhancing the susceptibility to localized corrosion and leading to SCC (Stress Corrosion Cracking) failure.